Rancang Bangun Sistem Keamanan Smart Door Lock Menggunakan E-KTP (Elektronik Kartu Tanda Penduduk) Dan Personal Identification Number Berbasis Arduino Mega R3 - Wisnu Wendanto; D Jayus Nor Salim; Dhika Wahyu Trisna Putra (Go Infotech: Jurnal Ilmiah STMIK AUB, 2019)
Existing house door security during conventional still uses door locks as keys and often cases of door burglary and theft occur and the majority of homeowners work so the lack of house supervision by the owner. So we need a more practical and efficient key and more security for door locks, from this problem the author has the idea to produce a safe and practical door safety device based on RFID by utilizing e-KTP as an RFID tag and Keypad as a PIN to secure the door of the house. This design uses an Arduino Mega R3 microcontroller. This tool consists of several main components, namely e-KTP, RFID reader, microcontroller, 4x4 Keypad, Relay, and Solenoid Door Lock. The e-KTP chip functions as a label of an object in which there is data about the object. RFID reader is used as a reader of information contained in e-KTP. The microcontroller as the main controller, 4x4 keypad as personal access number identification and solenoid door lock as the key. The test results can be concluded that the door security system uses e-KTP and this PIN is able to read the e-KTP ID with a maximum distance of 1cm with the MFRC522 sensor RFID reader which has a frequency of 13.56 MHz placed in plywood 1cm thick. The PIN runs well by entering the 6 digit pin code on the available keypad. As well as the Solenoid Door Lock as a door lock runs smoothly.